Technical Performance Analysis of a 1 MWp Grid-Connected Photovoltaic System in Pangkalan Kerinci, Indonesia Using PVsyst Simulation - Dedi Tri Laksono; Deni Tri Laksono; Monika Faswia Fahmi; Rien Afrianti; Nofri Dodi (Universitas Trunojoyo Madura, 2025)
The increasing demand for clean energy in Indonesia has accelerated the deployment of grid-connected photovoltaic (PV) systems. This study presents a technical performance analysis of a 1 MWp grid-connected PV system located in Pangkalan Kerinci, Indonesia, using the PVsyst v7.4.6 simulation software. The system comprises 1818 Trina Solar TSM-DE19-550Wp modules mounted on a fixed-tilt structure (2.2° tilt, 180° azimuth) with two SMA Sunny Central 400 MV-11 inverters (DC/AC ratio = 1.25). Meteorological data from Meteonorm 8.1 (1996–2015) was used to simulate annual irradiation and system output. The results show an annual energy production of 1,404,124 kWh, corresponding to a specific yield of 1,404 kWh/kWp/year. The Performance Ratio (PR) reached 82.75%, indicating high system efficiency under tropical climatic conditions. Loss analysis revealed that thermal losses (9.36%) and IAM losses (2.58%) were the dominant factors, while inverter losses accounted for 2.86%. Module mismatch and wiring losses were minimal at 2.15% and 1.5%, respectively. The high PR and low degradation assumptions confirm the suitability of the selected configuration for equatorial regions. This study provides a robust technical benchmark for similar PV installations in Sumatra and supports optimal design decisions for future utility-scale solar projects in Indonesia.